The Effect Of Current Ratio, Total Asset Turnover And Debt To Equity Ratio On The Financial Performance Of Manufacturing Companies Listed On The Indonesia Stock Exchange For The 2016-2020 Period - Devi Indah Juliani; Subur Karyatun; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine and analyze the effect of Current Ratio, Total Asset Turnover, Debt Equity Ratio, on performance finance of a Manufacturing Companies listed on the Indonesia Stock Exchange. Sources of research data using secondary data in the form of financial statements found on the website www.idx.co.id. The financial reports observed are the financial statements of Manufacturing companies for the year 2016-2020. The data of this study were analyzed on 10 manufacturing companies listed on the Indonesia Stock Exchange. In taking the sample for this study using purposive sampling method. The data analysis technique used is linear regression analysis and hypothesis testing using a T-test that has been processed in SPSS Version 21 to test the regression coefficients. Based on the results of the study, it was found that the Current Ratio and Debt Equity Ratio had a positive and significant effect on performance finance, Total Asset Turnover had a negative and insignificant effect on performance finance.